2018
DOI: 10.1111/jre.12612
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 gene polymorphisms and chronic periodontitis susceptibility: Evidence based on 33 studies

Abstract: The purpose of the meta-analysis was to investigate the potential association of interleukin-10 (IL-10) polymorphisms with susceptibility to chronic periodontitis (CP). A total of 33 studies involving 3487 cases and 4356 controls were identified through a search of multiple electronic databases (last search was updated on 19 July 2018).Three single nucleotide polymorphisms (SNPs) were included in the meta-analysis: -1082A>G(rs1800896), -819C>T(rs1800871), and -592C>A(rs1800872). Odds ratios (ORs) and their 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…−819 C/T, also displayed an association with chronic periodontitis in Caucasians and Latinos. 61,62 Additionally, single nucleotide polymorphism IL-10 −1082 A/G was associated with health in both of the same populations. 62 A study of Germans diagnosed with aggressive periodontitis found an association with single nucleotide polymorphism IL-10 rs61815643 and rs6667202.…”
Section: Interleukinsmentioning
confidence: 95%
See 1 more Smart Citation
“…−819 C/T, also displayed an association with chronic periodontitis in Caucasians and Latinos. 61,62 Additionally, single nucleotide polymorphism IL-10 −1082 A/G was associated with health in both of the same populations. 62 A study of Germans diagnosed with aggressive periodontitis found an association with single nucleotide polymorphism IL-10 rs61815643 and rs6667202.…”
Section: Interleukinsmentioning
confidence: 95%
“…61,62 Additionally, single nucleotide polymorphism IL-10 −1082 A/G was associated with health in both of the same populations. 62 A study of Germans diagnosed with aggressive periodontitis found an association with single nucleotide polymorphism IL-10 rs61815643 and rs6667202. 63 A validation study in Polish and German-Austrian populations confirmed these associations 63 .…”
Section: Interleukinsmentioning
confidence: 95%
“…A total of 457 studies were screened using the mentioned search strategy. After deleting duplicates, a record screen was performed and 16 case-control studies were finally selected [1731]. The search process and strategy of study selection are showed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of selected studies in meta-analysis, including our case-control study, are showed in Table 2 [31]. A total of 16 studies were included in the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis, Wang et al indicated that the −592C/A IL-10 gene polymorphism is related to PD susceptibility in Caucasians and Asians [50]. Another meta-analysis has shown that the −1082A/G polymorphism might be protective against CP in both Caucasians and Latinos, but the −819C/T and −592C/A polymorphisms might increase the risk of CP in Latinos [49].…”
Section: Interleukin 10mentioning
confidence: 99%